Pravna narava ustanovitvenih aktov kapitalskih družb in kategorizacija njihovih sestavin - Podgorelec, Peter (Pravnik, 2013)
The author discusses the legal nature and elements of the articles of association (hereinafter articles) of a company. The articles of a private limited company, as well as the articles of a stock corporation, are a contract sui generis most often referred to in theory as an organizational contract. Determination of its legal nature is important for the interpretation of its provisions, and it also helps to understand why the categorization of its elements is necessary. There are differences among the elements with regard to their legal meaning, which may be categorized as corporative, non-corporative, or indifferent. The shareholders of a private limited company have very broad autonomy in the regulation of the companys internal affairs, whilst such autonomy of the stock corporation shareholders is much more restricted. This, in turn, has an effect on the extent of the so-called indifferent elements, i.e., elements which may be qualified either as corporative or as non-corporative, depending on the preference of shareholders.
Keywords: gospodarske družbe; kapitalske družbe; pravna ureditev; statuti; ustanovitev